Perancangan Panduan Seminar Sosialisasi Sustainable MICE Bagi Pelaku Industri Pameran di Jawa Barat - Eko Susanto; Any Ariani Noor; Deddy Sobarna Sutaji; Dinarsiah Chendraningrum; Ratna Padmi Trihartanti; Santosa Sanjaya; Sri Hastuti; Tamara Herlinda Erwin (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The MICE industry is an essential part of the Indonesian tourism industry that has been affected by the Covid-19 pandemic, so sustainability is an important and relevant issue. As a follow-up to the Polban Community Service activities in 2019 and 2020, which focused on sustainable MICE issues, a joint design activity was carried out with the seminar guidebook for sustainable MICE socialization for ASPERAPI West Java. The electronic guidebook contains the stages of organizing a socialization seminar which is prepared using a participatory-collaborative method. This activity has resulted in an implementation guide that can be used and disseminated to members of ASPERAPI West Java.